Tenascin C Has a Modest Protective Effect on Acute Lung Pathology during Methicillin-Resistant Staphylococcus aureus-Induced Pneumonia in Mice - Mariska T. Meijer; Alex F. de Vos; Hessel Peters Sengers; Brendon P. Scicluna; Joris J. Roelofs; Chérine Abou Fayçal; Fabrice Uhel; Gertraud Orend; Tom van der Poll (Microbiology Spectrum, 2021)
ABSTRACT Tenascin C (TNC) is an extracellular matrix protein with immunomodulatory properties that plays a major role during tissue injury and repair. TNC levels are increased in patients with pneumonia and pneumosepsis, and they are associated with worse outcomes. Methicillin-resistant Staphylococcus aureus (MRSA) is a Gram-positive bacterium that is a major causative pathogen in nosocomial pneumonia and a rising cause of community-acquired pneumonia. To study the role of TNC during MRSA-induced pneumonia, TNC sufficient (TNC+/+) and TNC-deficient (TNC−/−) mice were infected with MRSA via the airways and euthanized after 6, 24, and 48 h for analysis. Pulmonary transcription of TNC peaked at 6 h, while immunohistochemistry revealed higher protein levels at later time points. Although TNC deficiency was not associated with changes in bacterial clearance, TNC−/− mice showed increased levels of TNF-α and IL-6 in bronchoalveolar lavage fluid during the acute phase of infection when compared with TNC+/+ mice. In addition, TNC−/− mice showed more severe pulmonary pathology at 6, but not at 24 or 48 h, after infection. Together, these data suggest that TNC plays a moderate protective role against tissue pathology during the acute inflammatory phase, but not during the bacterial clearance phase, of MRSA-induced pneumonia. These results argue against an important role of TNC on disease outcome during MRSA-induced pneumonia. IMPORTANCE Recently, the immunomodulatory properties of TNC have drawn substantial interest. However, to date most studies made use of sterile models of inflammation. In this study, we examine the pathobiology of MRSA-induced pneumonia in a model of TNC-sufficient and TNC-deficient mice. We have studied the immune response and tissue pathology both during the initial insult and also during the resolution phase. We demonstrate that MRSA-induced pneumonia upregulates pulmonary TNC expression at the mRNA and protein levels. However, the immunomodulatory role of TNC during bacterial pneumonia is distinct from models of sterile inflammation, indicating that the function of TNC is context dependent. Contrary to previous descriptions of TNC as a proinflammatory mediator, TNC-deficient mice seem to suffer from enhanced tissue pathology during the acute phase of infection. Nonetheless, besides its role during the acute phase response, TNC does not seem to play a major role in disease outcome during MRSA-induced pneumonia.